Sifat Fisik Pakan Kaya Serat dan Pengaruhnya terhadap Konsumsi - T Toharmat; E Nursasih; R Nazilah; N Hotimah; T Q Noerzihad; N A Sigit; Y Retnani (Media Peternakan, 2006)
Fibrous feeds vary in their physical properties. The experiment aimed to clarify the effect of physical properties of fibrous component in rations on feed intake and nutrient digestibility in goats. Rations were composed of 50% fibrous feed and 50% concentrate. The fibrous feed as treatments were as follows: napier grass (RG), rice straw (JP), cocoa pod (KC), mixed rice straw and coffee husk (JK), mixed napier grass, rice straw, coffee husk, and cocoa pod (CP). Rations were offered to four groups of 20 Etawah-grade goats weighing of 13.50±2.14 kg in a randomized block design. Physical properties of the fibrous components of ration and faeces, nutrients intake and digestibility and daily life weight gain were evaluated. Analysis of variance and correlation were applied to analyze data. Dry matter intake varied from 298-440 g/day. Goats offered KC ration had the highest intake. Low feed intake was associated with the low density of the fibrous component. Dietary fat digestibility decreased when the fibrous feed component had low capacity of oil adsorption. Young goats had life weight gain of 50-136 g/day, TDN requirement for maintenance and 50 g daily gain of 63.4 g and 131 g TDN, respectively. The results indicated that physical properties of fibrous component in the rations influenced dry matter intake and nutrients digestibility in growing goats. Key words : physical properties, intake, nutrient, digestibility, goat